News Representation and Sense of Belonging Among Multicultural Audiences - Park, Sora (2023)
This study seeks to understand the role of representation in news media, trust in news, and participation in multicultural audiences’ sense of belonging to society. A multimodal survey combining online, CATI, and CAPI methods was conducted in Australia at the end of 2021 and early 2022 (N = 1,084). The top five non-English language communities in Australia (Arabic, Cantonese, Italian, Mandarin, and Vietnamese) were included in the survey, of which n = 851 were born overseas. The findings reveal a significant link between the perception of sufficient representation in Australian news media, trust in news, confidence to participate in society, and sense of belonging. When multicultural audiences see themselves fairly and adequately represented in the news, they are more likely to trust the news and participate in the community by discussing the news and current affairs. This, in turn, leads to a stronger sense of belonging to society. We also found confidence in English and time spent in Australia were important factors contributing to perceptions of representation. While the length of stay has a positive impact on the perception of representation among those with high confidence in English, this perception is significantly lower among those who have lower confidence. This result confirms the significant role language proficiency plays in migrants’ experiences in the host country.